63.7k views
9 votes
√(-√(3)+√(3+8√(7+4√(3))))


\sqrt{ - √(3) + \sqrt{3 + 8 \sqrt{7 + 4 √(3) } } } \\


User Endofzero
by
4.6k points

1 Answer

8 votes

Explanation:

Given that: √[-√(3)+√{3+8√(7+4√(3))}]

= √[-√(3) + √{3+8√((√3)² + √(4)² + 2√(4*3))}]

= √[-√(3) + √{3 + 8√(√(3) + √(4))²}] [Since, {√(a) + √(b)}² = a+b + 2√(ab)]

= √[-√(3) + √{3 + 8√(√(3) + √(4))²}]

= √[-√(3) + √{3 + 8(√(3) + √(4))}]

= √[-√(3) + √{3 + 8(√(3) + √(2*2))}]

= √[-√(3) + √{3 + 8(√(3) + 2)}]

= √[-√(3) + √{3 + 16 + 8√(3)}]

= √[-√(3) + √{19 + 8√(3)}]

= √[-√(3) + √{16 + 3 + 2√(3*16)}]

= √[-√(3) + √{(16)² + (3)² + 2√(3*16)}]

= √[-√(3) + √{√(16)² + √(3)²}] [Since, {√(a) + √(b)}² = a+b + 2√(ab)]

= √{-√(3) + √(16) + √(3)}

= √{-√(3) + √(4*4) + √(3)}

= √{-√(3) + 4 + √(3)}

Now, cancel -√3 and +√3.

= √(4)

= √(2*2)

= 2

Answer: Hence, the simplified form of √[-√(3)+√{3+8√(7+4√(3))}] = 2.

Please let me know if you have any other questions.

User Chinthana
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.